Remarks about the Physical Development of Socially Orphaned Children - Goniprowska, Emilia; Mięsowicz, Irmina; Dobrzańska, Alina (Anthropological Review, 1985)
The results of anthropometric studies of infants from the Small Orphan's Home were compared with data of children from Warsaw families. The nutritional standards used in orphanages were analysed eliminating nutrition as the factor responsible for the differences in the development of socially orphaned children and children grown in a family.